Catch A Fire : The Autobiography - Brown, Melanie, 1975- (London Headline, 2002)
It's all here: the council estate childhood, the formation of the Spice Girls, the subsequent global domination, Geri's departure, the marriage - and acrimonious divorce - to Jimmy Gulzar, the birth of Phoenix Chi and the solo career. Not bad for a mixed-up girl from Leeds.
Include Illustration
Keywords: Singers -- Women singers -- Great Britain